2014
DOI: 10.1179/1743294413y.0000000199
|View full text |Cite
|
Sign up to set email alerts
|

On deposition of Waspaloy coatings by cold spray

Abstract: he deposition of pore free and highly adhered Ni and Co superalloy coatings is of great interest for engine design and gas turbine applications, both in oase of maintenance repair and overhaul operations as well for mechanical and chemical protection purposes in aeronautics and energy applications. This study would like to give a wide overview about the capability of cold spray technology on this topic: two different commercially available deposition systems, Sulzer-CGT Kinetiks 4000 and Plasma Giken PCS-1000,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Generally speaking, the particles impact velocity and temperature mainly depend on the initial parameters of the propellant gas [86]; Schmidt et al [87] showed that optimised particle injection and the high propellant gas temperature significantly increase the particle impact velocity and the temperature. In the last two decades a lot of studies have been carried out to better explain the interfacial bonding mechanisms as well as the effect of the deposition parameters on cold-sprayed coatings quality and microstructure [88][89][90][91][92][93]; the present review paper aims to summarise the main studies carried out up to now on the phenomena of the coating formation and the particle deformation mechanisms in cold spray processes.…”
Section: Introductionmentioning
confidence: 99%
“…Generally speaking, the particles impact velocity and temperature mainly depend on the initial parameters of the propellant gas [86]; Schmidt et al [87] showed that optimised particle injection and the high propellant gas temperature significantly increase the particle impact velocity and the temperature. In the last two decades a lot of studies have been carried out to better explain the interfacial bonding mechanisms as well as the effect of the deposition parameters on cold-sprayed coatings quality and microstructure [88][89][90][91][92][93]; the present review paper aims to summarise the main studies carried out up to now on the phenomena of the coating formation and the particle deformation mechanisms in cold spray processes.…”
Section: Introductionmentioning
confidence: 99%
“…b Microporosity due to lack of particle-particle bonding; micrography of Waspaloy coatings deposited by cold spray. 9 (c) Porosity due to particle removal during preparation of a specimen coated by Stellite 31 + 10 wt-% of AISI 316L. Red dots emphasise each kind of defects multi-alloy coatings as in this case, a certain lack of cohesion in coating microstructure leads to particle abrasion and removal during preparation.…”
Section: Resultsmentioning
confidence: 99%
“…5 In recent years, cold gas dynamic spray (CS) is receiving an increasing consideration because of its low spraying temperature and opportunities in the deposition of both metal-based oxygen sensitive and high strength metal-based materials, such as Stellite 6, Inconel 718, Waspaloy and aluminium. [6][7][8][9] CS is a thermal-spray technique but it remains a solidstate powder deposition process avoiding melting or partial melting of spraying particle and preventing the heat-affected zone. 10 Thanks to this advantage, ductile metallic coatings as copper and aluminium were used in restoring application for aircraft structural parts and injection moulding dies.…”
Section: Introductionmentioning
confidence: 99%
“…However, radially injected particles can either be directed into the gas in the upstream (high-pressure) section or the downstream (lowpressure) section of the nozzle, relative to the throat. Generally, CGDS processes can operate at temperatures between room temperature up to~1000°C and pressures up to 5 MPa ( Ref 7,9).…”
Section: Introductionmentioning
confidence: 99%